Collagen isolation and characterization from Sardinella longiceps (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Collagen is a fibrous protein that is primarily used in the pharmaceutical and biomedical industries. This study isolates and characterizes type-1 collagen from Sardine longiceps (scales, skin, and muscle).  Materials and Methods: Collagen was isolated from S. longiceps using two methods: acid-solubilized collagen and pepsin-solubilized collagen. Sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS–PAGE) was used to estimate the molecular weight of isolated collagen. Ultraviolet (UV)-visible spectrophotometry analysis was used to confirm the collagen extracted (type-I collagen). The functional groups of isolated collagens were identified using fourier transform infrared (FTIR) analysis. The X-ray diffraction (XRD) technique was used to investigate the crystallinity of isolated collagen. The high-pressure liquid chromatography (HPLC) technique was used to study the amino acid composition.  Results: SDS–PAGE of S. longiceps revealed molecular weights ranging from 116 kDa for α-2 to 97 kDa for α-1. UV-visible spectra showed an absorbance value below 300 nm, and the results confirmed type-I collagen. FTIR showed major functional groups like amide A, B, I, II, and III. XRD determined the crystallinity of isolated collagen. The HPLC results showed the presence of higher glycine content, followed by proline and hydroxyl proline in the extracted collagen.  Conclusion: The overall study confirmed that fish waste materials (scales, skin, and muscles) could be used as an alternative source for collagen.J. Adv. Vet. Anim. Res., 8(4): 679–686, December 2021http://doi.org/10.5455/javar.2021.h560